Pengaruh Kualitas Layanan, Makanan, Harga, dan Lingkungan terhadap Loyalitas melalui Kepuasan di Restoran Padang Cahaya Delima - Widya Syahputri; Sugiyanto (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Padang Cahaya Delima Restaurant, which is located in the Tangerang area, is a culinary destination that offers delicious Padang specialties. This research aims to determine the influence of service quality, food quality, physical environment prices on customer satisfaction through customer loyalty at Cahaya Delima restaurants in the Tangerang area. Data collection was obtained through a questionnaire distributed online in April 2024. Data analysis in this research used the Partial Least method. Square (SEM PLS) with a sample size of 230 respondents. The results of data processing show that service quality, food quality, price have a positive effect on customer satisfaction, but the physical environment does not have a positive effect on customer satisfaction. Physical environment, price, food quality have a positive effect on cust omer loyalty, but customer satisfaction and food quality do not have a positive effect on cstomer loyalty.